Pembelian Impulsif di Kalangan Gen Z saat Flash Sale: Peran Mediasi Emosi dan Peran Moderasi Adiksi Media Sosial - Asriadi, Asriadi; Tambaru, Rachman; Evrianti, Hesti (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study aims to explore the impact of flash sales that influence online impulse buying on ​​Gen Z, by placing emotions as a mediating variable and social media addiction as a moderating variable. Data collection was carried out using a purposive sampling technique, on 120 Gen Z people domiciled in Palu City. Data analysis processing utilized structural equation modeling (SEM) techniques processed through Smart PLS. Based on the results, it was revealed that flash sales showed a positive and significant relationship both on emotions and on online impulsive buying, while emotions showed a positive and significant impact on online impulsive buying. Furthermore, emotions were shown not to provide a significant mediating effect between social media addiction and online impulsive buying; meanwhile, social media addiction was shown to significantly moderate the effect of flash sales on online impulsive buying.